Coronary Artery Aneurysms and Acute Coronary Syndrome: An Interventionalist’s Dilemma - Nauman Khalid; Sundeep Kumar; Preetham Muskula; Haris Muhammad; Tarek Helmy (Methodist DeBakey Cardiovascular Journal)
We report three cases of coronary artery aneurysm (CAA) in adults who presented with acute coronary syndrome. Two of these patients did not have traditional coronary artery disease risk factors. Management of CAA poses a significant challenge to interventionalists. We discuss the etiologic mechanisms, risk factors, pathophysiology, and diagnosis using angiography, intravascular ultrasound, and coronary computed tomography. We also highlight management options, including medical therapy and catheter-based interventions such as stenting, coil embolization, stent-assisted coil embolization, and surgical exclusion.